The iterative solutions of nonlinear fractional differential equations - Zhang, Xinguang; Liu, Lishan; Wu, Yong Hong; Lu, Yinan (Elsevier Inc., 2013)
By means of monotone iterative technique, the existence and uniqueness of the positive solution for a fractional differential equation with derivatives are established, and the iterative sequence of the solution, an error estimation and the convergence rate of the positive solution are also given.